Interespecies effect of sequential human medium use in the production of blastocysts of female ovis canadensis mexicana by interspecies handmade cloning - Vazquez-Avendaño, José Roberto; Hernández-Martínez, Sarahí; Hernández-Pichardo, José Ernesto; Rivera-Rebolledo, Juan Arturo; Ambriz-García, Demetrio Alonso; Navarro-Maldonado, María del Carmen (Instituto de Ecología, A.C., 2017)
Effect of sequential human medium use in the production of blastocysts of female Ovis canadensis mexicana by interspecies handmade cloning. Faced to the notable problem that a significant number of world wild species are endangered, some biotechnologies such as the interspecific somatic cell nuclear transfer (SCNT), have been applied to raise their reproduction and conservation. This technology has been successfully applied by producing embryos and live offspring in some of these species. However, the interspecific SCNT still has to solve problems such as the low embryo production and  offspring survival rates (3-6%). These problems, among others, involve a high incidence of embryo fragmentation and in order to solve them, most studies are now aimed to determine the effect of different culture media or supplements used for in vitro embryo production. Therefore, the aim of the present study was to use a variant of the interspecific SCNT technique (Handmade cloning-HMC) for embryo production, determining the effect of human sequential media in the endangered Mexican wild sheep O. c. mexicana. Results indicate that the embryo production increased when using human sequential media, allowing the  mbryos to reach the blastocyst stage (16% vs. 0%, P < 0.05). This is the first study that reports the successful cloning of female O. c. Mexicana embryos in Mexico.